2023
DOI: 10.1111/psyg.12969
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health literacy and health empowerment on quality of life in the elderly

Abstract: Background: This study was conducted to determine the effect of health literacy and health promotion on quality of life in the elderly. Method: This descriptive and cross-sectional study was conducted with 981 elderly individuals aged 65 years and older in Turkey. 'Introductory Information Form', 'Health Literacy Scale', 'Elderly Health Empowerment Scale' and 'Quality of Life Scale for the Elderly' were used to collect data. The research data were analyzed by Structural Equation Modelling using SPSS 22.0, AMOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Additionally, greater income implies solitary older adults can access and utilize more medical resources, reducing mental health risks. Internet use also clearly benefits the psychological well-being of solitary older adults, aligning with findings by Zhao et al ( 35 ). The internet provides solitary older adults platforms for communication and learning, fulfilling the need for continued socialization ( 20 ).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, greater income implies solitary older adults can access and utilize more medical resources, reducing mental health risks. Internet use also clearly benefits the psychological well-being of solitary older adults, aligning with findings by Zhao et al ( 35 ). The internet provides solitary older adults platforms for communication and learning, fulfilling the need for continued socialization ( 20 ).…”
Section: Discussionsupporting
confidence: 88%
“… 4 Studies have also found that low health literacy is associated with reduced quality of life, increased healthcare costs, heightened doctor-patient conflicts, and an increased societal burden. 5 , 6 Health literacy generally refers to the ability to obtain, read, understand, and apply health information to make sound health decisions and follow treatment. 7 Various media form the primary carriers of health information dissemination.…”
Section: Introductionmentioning
confidence: 99%